Work Relations from the Perspective of Max Weber and Michel Crozier (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract: Studying work relations represents as a crucial cognitive subject, which is intended to decipher the relationship network between actors within organization. The purpose of this study is therefore to address work relations concepts, types and objectives relying on two opposing theories, namely Max Weber's ideal-type bureaucracy and Michel Crosier’s strategic analysis. Results showed that Max Weber strongly believes that work relations can exist only inside the formal system which is the one to control and limit them while Crozier believes that work relations are no more than a game between two sides based on strategies guaranteed by the resources the actor possesses.Keywords: Work Relations, collective action, Ideal-Type Bureaucracy, Strategic Analysis, authority.ملخص :لا يزال الرهان قائما على أهمية دراسة علاقات العمل، كموضوع معرفي هام يهدف إلى فك رموز الفعل الجماعي داخل المنظمة. وبذلك فإن الغرض من هذه الدراسة، هو محاولة التطرق إلى علاقات العمل مفاهيما وأنواعا وأهدافا، وعرض وجهتي نظر مختلفة لنفس الموضوع انطلاقا من البيروقراطية المثالية لماكس فيبر والتحليل الاستراتيجي لميشال كروزيه. أين أظهرت النتائج أن ماكس فيبر يؤمن بقوة بأن علاقات العمل لا يمكن أن تخرج على النظام الرسمي وهو النظام الذي يتحكم فيها ويحد منها، بينما يعتقد كروزيه أن علاقات العمل ليست أكثر من لعبة بين أطراف فاعلة توظف استراتيجيات تضمنها لهم الموارد التي يمتلكونها.كلمات دالة علاقات العمل ، الفعل الجماعي ، البيروقراطية المثالية ، التحليل الاستراتيجي ، السلطة